Seroprevalence of African horse sickness virus and equine encephalosis virus in equids and abundance of Culicoides midges in Namaqualand, South Africa - thinkels@hotmail.com (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Tropical Diseases))--University of Pretoria, 2012.